If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7(n-1)=-(3+n)
We simplify the equation to the form, which is simple to understand
7(n-1)=-(3+n)
Reorder the terms in parentheses
+(+7n-7)=-(3+n)
Remove unnecessary parentheses
+7n-7=-(+3+n+)
Remove unnecessary parentheses
+7n-7=-3-1n
We move all terms containing n to the left and all other terms to the right.
+7n+1n=-3+7
We simplify left and right side of the equation.
+8n=+4
We divide both sides of the equation by 8 to get n.
n=0.5
| k^2+5k-9=0 | | y=-1x^2+29x+12 | | 4r-10= | | 770=3x+77 | | x^2+x=-c | | 5.2+1.7n=1.12 | | 2m+k+3m+2k= | | k+1=k^2+k+c | | 3w+14=50 | | k=-2k^2-k | | 8x+7=5x-21 | | 3(p+4)=24 | | 4y+6y-5=10y-5 | | 5k+40L-35m= | | Sqrt(7x+44)=x | | Ix+7I=2 | | 9-7(5x-8)=63-9x | | 6(x+1)=2(3x+1)+4 | | 11x+5-3x+7= | | x^3+4*x^2+-11*x+30=0 | | 15(a)=225 | | 5x+3=7+5x | | 8(x-3)=-3x-17 | | -7(3x-5)+8=-21x+43 | | 11x-5-3x+7= | | 41=2x+3x+5 | | 3x+20=5x-24 | | 3+-2t=0 | | 4y-4=8x | | 3x-3=3(x-4) | | 3y+4=4+3y | | -5+-1t=0 |